(3TQM GdQSGdI GdYVOjIs - (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje gPg aGFOI GdeTGQ Edjg HgPg CeG Jdc GdYHGQGJ GdeNUhUI fRdJ efRdI GdeMShS s
(3BNQgG (B:s
(3dGjQjHc Ci dGjhbYc ai QjHI hTc JYGhQ CdaGX Ci JGhHgG HYVgG ecGf HYV Ch GdeYJHQ GdhVY JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B119 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B527s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs